SAVI and DLPS learning models on mathematical problem solving - Syazali, Muhamad; Afandi, Kiki; Ramadhani, Rahmi (Universitas Islam Negeri Raden Intan Lampung, 2022)
Problem-solving ability is an skills related to mathematical characteristics which instructors need to encourage educators to be able to solve problems. This process certainly uses the right learning model to reach the target in accordance with the curriculum. This study aims to compare the influence of Somatic, Auditory, Visualization, and Intellectually (SAVI) and Double-loop Problem-solving (DLPS) methods in influencing mathematical problem solving skills. This study uses quantitative types with data analysis techniques using the T test. The results of this study are that there is an average value in the SAVI learning model of 77.7 while the average value of the DLPS learning model is 77.3. The conclusion can be drawn that the SAVI and DLPS learning models have the same effect on problem solving skills.